The relative labour market performance of former international students: Evidence from the Canadian National Graduates Survey - Zong Jia Chen; Mikal Skuterud (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2017)
Canada is increasingly looking to international students as a source of postsecondary tuition revenues and new immigrants. By 2014, international students accounted for 10% of graduates from Canadian postsecondary institutions, up from 3% in 2000, and 11% of new permanent residents, up from 7% in 2010. This article compares the labour market performance of former international students (FISs) entering the Canadian labour market during the first decade of the 2000s to their Canadian-born-and-educated (CBE) and foreign-born-and-educated (FBE) counterparts. We find that FISs outperform FBE immigrants by a substantial margin and un- derperform CBE individuals graduating from similar academic programs by a relatively modest margin. We also find some limited evidence, particularly among women, of a deterioration in FIS outcomes through the 2000s relative to both comparison groups. We argue that this de- terioration is consistent with a quality tradeoff as postsecondary institutions and governments have reached deeper into international student pools to meet their demands for students and new immigrants without a commensurate increase in their supply.
Keywords: I23; J61; J31; 330; International students; labour market integration; immigrant selection policy